L2 ACQUISITION OF PROSODIC PROPERTIES OF SPEECH RHYTHM. Issue 2 (20th May 2014) - Li, Aike; Post, Brechtje
<x content-type="archive" xml:space="preserve">Abstract</x> This study examines the development of speech rhythm in second language (L2) learners of typologically different first languages (L1s) at different levels of proficiency. An empirical investigation of durational variation in L2 English productions by L1 Mandarin learners and L1 German learners compared to native control values in English and the learners' L1s showed that the L1 groups followed comparable developmental paths in their acquisition of vocalic variability and accentual lengthening. However, the two L1 groups diverged in the proportion of vocalic materials in their L2 utterances, exhibiting L2 acquisition patterns that are consistent with direct transfer from the L1. The results support a multisystemic model of L2 rhythm acquisition in which the various linguistic-systemic properties that contribute to speech rhythm are acquired at different proficiency levels and depend on different acquisition processes with respect to L1 influence and universal effects. We conclude that theories of L2 phonology need to be able to accommodate the multisystemic nature of L2 prosodic acquisition. Additionally, L2 phonological acquisition theories, and SLA theories more generally, should take into account the nonuniform manner in which the various prosodic properties of the interlanguage reflect L1 transfer effects as well as universal constraints on acquisition.